Remote Patient Monitoring – Ein Blick über den Atlantik und was wir von den USA lernen können - Linea Schmidt; Anastasios Mastroanastasiou; Ariel Dora Stern (Wirtschaftsdienst, 2025)
The digital transformation of the healthcare system enables personalised therapies and performance-based remuneration thanks to comprehensive data. Smart regulation must avoid the threat of data-based monopolies through proprietary data access, e.g. by the obligation of powerful platforms to share data. In Germany, short-term remuneration incentives, individualised solutions and a lack of infrastructure too often hinder the emergence of digital innovations.Remote Patient Monitoring (RPM) ermöglicht die digitale Überwachung von Patient:innen im häuslichen Umfeld und gewinnt angesichts des Fachkräftemangels im Gesundheitswesen gepaart mit dem demografischen Wandel zunehmend an Bedeutung. In Deutschland ist RPM bisher vorrangig bei Herzinsuffizienz erstattungsfähig, während die USA bereits ein breiteres Einsatzspektrum sowie eine stärkere Einbindung von nicht-ärztlichen Berufsgruppen wie Apotheken zeigen. Studien belegen positive Effekte auf klinische Ergebnisse und Versorgungseffizienz. Für Deutschland bietet die Verknüpfung von Echtweltdaten mit Abrechnungs- und klinischen Daten die Chance einer fundierten Bewertung des medizinischen und ökonomischen Nutzens von RPM. – – Remote Patient Monitoring (RPM) enables the digital monitoring of chronically ill patients in their home environments and is becoming increasingly important due to the shortage of skilled labour and demographic change. In Germany, RPM is currently primarily reimbursable for heart failure, while the USA is already showing a broader range of applications and greater involvement of pharmacies. Studies have shown positive effects on clinical outcomes and care efficiency. For Germany, the linking of real-world data with billing and clinical data offers the opportunity for a well-founded evaluation of the medical and economic benefits of RPM.
Keywords: H51; I11; I18; 330